2015
DOI: 10.7868/s0016675815100100
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility Loci for Umbilical Hernia in Swine Detected by Genome-Wide Association

Abstract: Umbilical hernia (UH) is a complex disorder caused by both genetic and environmental factors. UH brings animal welfare problems and severe economic loss to the pig industry. Until now, the genetic basis of UH is poorly understood. The high-density 60K porcine SNP array enables the rapid application of genome-wide association study (GWAS) to identify genetic loci for phenotypic traits at genome wide scale in pigs. The objective of this research was to identify susceptibility loci for swine umbilical hernia usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Ding et al (2009) [11] were the first to identify regions related to the occurrence of umbilical hernias in pigs. Afterwards, other studies also identified regions related to umbilical hernias in pigs [5,12,13]. Six of the genes DE in our study were mapped to QTL regions already described in the literature for umbilical hernias in pigs: ACER2, SLC2A6, PTGS1, LGALS3, KANK3 and FOS.…”
Section: Immune Systemsupporting
confidence: 54%
See 3 more Smart Citations
“…Ding et al (2009) [11] were the first to identify regions related to the occurrence of umbilical hernias in pigs. Afterwards, other studies also identified regions related to umbilical hernias in pigs [5,12,13]. Six of the genes DE in our study were mapped to QTL regions already described in the literature for umbilical hernias in pigs: ACER2, SLC2A6, PTGS1, LGALS3, KANK3 and FOS.…”
Section: Immune Systemsupporting
confidence: 54%
“…Some studies have been performed to identify the genetic factors involved in the development of umbilical hernias, and QTL regions, SNPs and candidate genes associated with the appearance of this defect have been detected [5,[11][12][13]. In this study, using RNA-Seq, we sequenced the umbilical ring transcriptome to discover possible genes involved in the occurrence of umbilical hernias in pigs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…), single nucleotide polymorphisms (SNPs; Liao et al . ) and copy number variations (CNVs; Long et al . ).…”
Section: Genotypes Of Eight Snps In Coding Regions Of the Pig Capn9 Gmentioning
confidence: 99%